KRAS and MT-CO1 genes in colorectal cancer: a molecular investigation: KRAS and MT-CO1 expression in CRC - A. Hama, Harmand; Hasan, Bestoon S.; Barzngy, Basak; Abdulla, Saman S.; Karim, Abdulkarim Y.; Khailany, Rozhgar A.; Miasko, Monika; Dabrowski, Janusz M.; Pucelik, Barbara (Cellular and Molecular Biology, 2023)
Colorectal cancer (CRC) is the third leading cause of cancer-related deaths worldwide. The tumor suppressor gene MT-CO1, and Kristen Rat Sarcoma Virus (KRAS), an oncogene are primarily responsible for controlling cell apoptosis, cell cycle arrest, and cell proliferation, and any irregularities in these genes could lead to cancer. This study aims to examine the expression of KRAS and MT-CO1 in CRC biopsy specimens and investigate their relationship with one another in CRC patients residing in the Erbil city of Kurdistan Region, Iraq. The study involved categorizing 42 sets of colorectal cancer tissues and their corresponding controls based on their types and patients' clinical characteristics. The expression of KRAS and MT-CO1 in the samples was assessed using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR), with statistical significance set at p<0.05. The expression of KRAS was found to be significantly higher in CRC compared to the control (n=42, p=0.0001). On the other hand, the expression of MT-CO1 did not exhibit significant differences compared to the control group with a p-value of 0.12. Furthermore, the Chi-square and correlation analysis results depicted that MT-CO1 expression negatively correlates with KRAS expression (p= 0.0001, r= -0.047) in CRC tissues. In conclusion, the variation in the expression of KRAS and MT-CO1, and their correlations could potentially serve as a good indicator in the detection and prognosis of CRC, which might lead to better translational research on the same. However, for a better understanding of the underlying mechanisms, further analysis is required.